Catalogue and typification of the Moroccan taxa published by Carlos Pau - Nualart, Neus; Soriano, Ignasi; Pérez Prieto, David; Ibáñez, Neus (Phytotaxa, 2021)
Carlos Pau was one of the first Spanish botanists interested in the flora of northern Morocco. He proposed 421 taxa for this area, including some illegitimate names and nomina nuda. A complete and annotated catalogue of names by Pau for Moroccan taxa is presented here. For all of them, the typification and synonymy have been evaluated. For 63 taxa the holotype is indicated, and 206 taxa are typified here. The main collection of Pau and most types are preserved in Herb. MA, but many types have also been found in Herb. BC and other European herbaria.